2021
DOI: 10.1186/s12903-021-02024-x
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitor concentrations in the saliva of individuals experiencing oral dryness

Abstract: Background Oral dryness is a common symptom that may interfere with swallowing, chewing, and taste. The most common reason for oral dryness is hyposalivation. Some individuals experiencing oral dryness do not have hyposalivation, however, and the reverse is also true. Here, we focused on healthy individuals with a lower salivary flow rate and evaluated the relationship between the perception of oral dryness and salivary parameters to clarify the cause underlying the perception of oral dryness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In terms of clinical relevance, histone modification has previously been suggested as a new treatment in pSS [ 43 ], and the results from the present study indicate that they may play a role in other dry mouth conditions as well. Furthermore, cystatins have been reported to be in lower concentrations in subjects with xerostomia compared to subjects with similar salivary flow rates [ 44 ]. The current study suggests that this should be explored further, and may help in understanding the lack of correlation between symptoms and objective findings in dry mouth [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical relevance, histone modification has previously been suggested as a new treatment in pSS [ 43 ], and the results from the present study indicate that they may play a role in other dry mouth conditions as well. Furthermore, cystatins have been reported to be in lower concentrations in subjects with xerostomia compared to subjects with similar salivary flow rates [ 44 ]. The current study suggests that this should be explored further, and may help in understanding the lack of correlation between symptoms and objective findings in dry mouth [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most inhibitors are highly specific for single or several related proteinases whereas the α-2-macroglobulin and the alpha 1-proteinase (α-1-antitrypsin) have a broader specificity [19]. Mucosal swabs and saliva also contain a number of proteins, including mucin, histatin, cystatin, statherin, amylase, lingual lipase, secretory immunoglobulins and proline-rich protein [20]. These proteins maintain tooth and mucosal integrity, mucosal immunity and are involved in digestion, lubrication, buffering and antibacterial activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cystatins, which are salivary cysteine protease inhibitors, have antimicrobial and protease inhibitory properties [ 12 , 25 , 26 ], however, anti-IAV activity of cystatins is unknown. The findings of the present study demonstrated high concentrations of cystatin family members in SMSL saliva that positively correlated with anti-IAV activity.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary proteins were identified by mass spectrometry according to previously described methods [ 16 , 25 ]. For ultrafiltration, 300 µL of each type of saliva was diluted with 200 µL of 100 mM Tris/HCl buffer (pH 8.5), transferred to a 3-kDa-cutoff Millipore ultrafiltration device (Merck KGaA, Darmstadt, Germany), and centrifuged at 14,000 g at 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%